Pharyngoesophageal diverticulum mimicking thyroid nodules: Some interesting ultrasonographic signs - Bai, Zhiqun; Wang, Xuemei; Zhang, Zhen (Frontiers in Oncology, 2023)
Objective: To analyze the ultrasonographic features of pharyngoesophageal diverticulum (PED) mimicking thyroid nodules and to explore the clinical value of ultrasonography in the diagnosis of PED. Method: The sonographic findings of 68 patients with PED were retrospectively reviewed. According to the diverticulum echo intensity characteristics, the lesions were divided into solid nodular diverticulum, gas-containing nodular diverticulum, liquid-containing nodular diverticulum, and atypical diverticular changes; and the ultrasonographic manifestations were compared among the four groups. Results: 30/68 were solid nodular diverticula. The diverticulum cavity was oval or elliptic with a clear border, and the diverticulum wall suggested exhibited a typical hyper-hypo-hyper-echogenic pattern. The diverticulum wall and esophageal wall were seen to be continuous if multiple sections were scanned, and hypoechoic walls showed punctate blood flow. 29/68 diagnosed with air-containing nodular diverticulum, lesions appeared with gas-like hyper-echogenicity internally, with some amount of gas and change in the tail pattern during swallowing. 6/68 patients were diagnosed with liquid-containing nodular diverticulum ,and the main ultrasonic manifestations were an anechoic internal diverticulum cavity that was clearly bounded from the thyroid but continuous with the esophageal wall, with a typical hyper-hypo-echoless pattern from the outside to the inside. Another 3/68 were found to have atypical diverticular changes, regional convexities of the esophageal wall with unfashioned nodules. The convex segment was continuous with the hyper-hypo-echogenic esophageal wall and could be seen on slitting scanning. Conclusion: Overall, PEDs mimicking thyroid nodules have specific ultrasonographic features. Familiarity with them can avoid missed diagnoses and misdiagnoses.